2022
DOI: 10.1002/mus.27524
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and pulmonary findings in dysferlinopathy: A 3‐year, longitudinal study

Abstract: Introduction/Aims: There is debate about whether and to what extent either respiratory or cardiac dysfunction occurs in patients with dysferlinopathy. This study aimed to establish definitively whether dysfunction in either system is part of the dysferlinopathy phenotype. Methods: As part of the Jain Foundation's International Clinical Outcome Study (COS) for dysferlinopathy, objective measures of respiratory and cardiac function were collected twice, with a 3-y interval between tests, in 188 genetically confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Perhaps the clearest overlap is with the sarcoglycanopathies [ 39 , 40 ], although these tend to show earlier loss of ambulation [39] . In contrast, dilated cardiomyopathy and ventilatory needs are uncommon in subtype R1 [ 41 , 42 ], R2 [43] and R12 [44][45][46] . Furthermore, anoctaminopathy and dysferlinopathy are associated with a later onset; median 35 years (common type) [44] and 19 years [47] , respectively.…”
Section: Clinical Datamentioning
confidence: 99%
“…Perhaps the clearest overlap is with the sarcoglycanopathies [ 39 , 40 ], although these tend to show earlier loss of ambulation [39] . In contrast, dilated cardiomyopathy and ventilatory needs are uncommon in subtype R1 [ 41 , 42 ], R2 [43] and R12 [44][45][46] . Furthermore, anoctaminopathy and dysferlinopathy are associated with a later onset; median 35 years (common type) [44] and 19 years [47] , respectively.…”
Section: Clinical Datamentioning
confidence: 99%
“…Therefore, given that dysferlin has been implicated in multiple mechanisms known to support skeletal muscle physiology, it is clear why dysferlin mutations primarily manifest in skeletal myopathy (Bushby et al., 1998; Liu et al., 1998). However, clinical observations showed that some dysferlinopathy patients presented with a cardiac phenotype (Moore et al., 2022; Nishikawa et al., 2016; Wenzel et al., 2007). Like skeletal muscle, cardiac muscle contains extensive t‐tubule networks with associated EC coupling proteins, which facilitate the fast and synchronous rise in intracellular Ca 2+ necessary for a healthy heartbeat (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Dysferlin deficiency leads to progressive skeletal muscle degeneration and atrophy. 11,12 Restoring dysferlin expression is likely the only curative solution and clustered regularly interspaced short palindromic repeats – associated protein 9 (CRISPR/Cas9) methodology would have the greatest utility.…”
Section: Introductionmentioning
confidence: 99%